Le Borinage - Lemonnier, Camille; Renard, Marius; Decamps, Conzales; Van Hasselt, Valentin; Ghislain, Oscar (Renard & Vilain, 1902)
"par Camille Lemonnier, Marius Renard, Conzales Decamps, Valentin Van Hasselt, Oscar Ghislain ; illustré par Constantin Meunier, Marius Renard"